2017
DOI: 10.1097/eja.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Does deep neuromuscular block affect pain after laparoscopic surgery?

Abstract: Editor,In a recent issue of the European Journal of Anaesthesiology, Madsen et al. 1 presented a randomised controlled trial, evaluating the effect of deep neuromuscular blockade and low-pressure pneumoperitoneum in laparoscopic hysterectomy. The authors concluded that deep neuromuscular blockade and low-pressure pneumoperitoneum (8 mmHg) reduced the incidence of postoperative shoulder pain as compared to standard pressure pneumoperitoneum (12 mmHg) with standard neuromuscular blockade. This finding is in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In bariatric surgery, deep relaxation has advantages for surgeon and patient. Compared to the moderate neuromuscular blockade, deep neuromuscular blockade produced stable and improved surgical conditions with less postoperative pain 15 . Deep neuromuscular blockade was used in all patients, and this may be a factor that contributed equally among groups to reduce pain score in the PACU.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In bariatric surgery, deep relaxation has advantages for surgeon and patient. Compared to the moderate neuromuscular blockade, deep neuromuscular blockade produced stable and improved surgical conditions with less postoperative pain 15 . Deep neuromuscular blockade was used in all patients, and this may be a factor that contributed equally among groups to reduce pain score in the PACU.…”
Section: Discussionmentioning
confidence: 96%
“…Deep neuromuscular blockade was used in all patients, and this may be a factor that contributed equally among groups to reduce pain score in the PACU. However, intraabdominal pressure (pneumoperitoneum) was maintained in 15mmHg, which limited the result of the deep neuromuscular blockade to decrease the incidence of pain 15 . Although a previous study 16 found reduced recovery times in the PACU, the current study groups exhibited no differences when delayed discharge from the PACU and recovery time longer than 90 minutes were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Dies änderte sich erst vor einigen Jahren mit der Einführung von Sugammadex; erstmals konnten nun auch tiefe neuromuskuläre Blockaden antagonisiert werden [11]. Es ist daher nicht überraschend, dass in der Folge der mögliche klinische Nutzen einer Vollrelaxierung Gegenstand zahlreicher Untersuchungen wurde [12]. Grundlage für die Annahme, dass eine tiefe Blockade möglicherweise die Operationsbedingungen verbessern könnte, ist die Resistenz des Diaphragmas gegenüber der Wirkung von Muskelrelaxanzien; das Diaphragma ist bereits zu einem Zeitpunkt wieder vollständig neuromuskulär erholt, an dem der M. adductor pollicis noch eine ausreichende neuromuskuläre Blockade aufweist [13].…”
unclassified